Современная система подготовки банковских кадров и их оценка в Узбекистане - Шермухамедов, О.А.; Мамаева, М.Э. (Культура народов Причерноморья, 2013)
В статье рассматриваются вопросы повышения квалификации банковских работников.
Как показали исследования, профессиональная мобильность имеет определенные возрастные границы и
разную интенсивность. Так, высвобождаемые банковские работники старших возрастов имеют
меньшую способность и склонность к перемене труда в банке. Широким оказывается спектр новых
банковских профессий, осваиваемых в процессе переподготовки. Сравнение прежней и новой банковских
профессий позволяет оценить прежде всего степень родства, их своего рода близость и стоящую за
всем этим глубину переподготовки работников банка, сроки и затраты средств на ее проведение.
Постоянно проводимый анализ позволяет выявить складывающиеся тенденции и оценить их и это
способствует принятию более обоснованных управленческих решений по регулированию этого процесса. У статті розглядаються питання підвищення кваліфікації банківських працівників. Як
показали дослідження, професійна мобільність має певні вікові межі і різну інтенсивність. Так,
вивільняються банківські працівники старшого віку мають меншу здатність і схильність до зміни праці
в банку. Широким виявляється спектр нових банківських професій, освоюваних у процесі перепідготовки.
Порівняння колишньою і новою банківських професій дозволяє оцінити насамперед ступінь споріднення,
їх свого роду близькість і що стоїть за всім цим глибину перепідготовки працівників банку, терміни і
витрати коштів на її проведення. Постійно проводиться аналіз дозволяє виявити складаються
тенденції і оцінити їх і це сприяє прийняттю більш обґрунтованих управлінських рішень з регулювання
цього процесу. The article considers the issues of improving professional skill of bank employees. As the research
has shown, professional mobility has certain age limits and different intensity. Thus, redundant bank employees
of older age group have lesser ability and propensity to adapt to the changing work in a bank. There is a wide
range of new bank professions that can be mastered in the course of retraining. The comparison of the former
and new bank professions allows estimating, first of all, what they have in common in order to determine the
required new job for retraining of bank staff, terms and expenses for its carrying out. The analysis carried out
constantly allows revealing and estimating the current tendencies, which assist to make more sound
administrative decisions on regulation of this process.
Professional skills training, as well as acquisition of knowledge, skills, and abilities are the result of
professional activity. Specially organized training allows achieving the objective over the shorter period of time.
Professional skills training of bank employees is directed towards consecutive advancement of professional
knowledge, skills, as well as growth of professional experience.
The characteristic feature of professional skill training of bank employees is in the fact that the audience already
possessing certain knowledge and practical skills of work performance can crucially assess the teaching
material and get that information which is necessary for them in their professional activity.